The correlation between honesty-humility and attitude toward counterfeit luxury - Nina Reinhardt; Marc-André Reinhard; Gerrit Bittner-Fäthke (Italian Journal of Marketing, 2023)
This research focuses on the relation between Honesty-Humility and attitude toward counterfeit luxury. Honesty-Humility is defined as the tendency to be fair in dealing with others. Given that the act of knowingly purchasing a counterfeit could be judged as morally questionable, immodest, and manipulative, we predicted that people lower in Honesty-Humility would report more positive attitudes toward counterfeit luxury. Given that related research from behavioral research revealed Honesty-Humility to be the key predictor for unethical behavior, we further predicted this association to remain robust even when controlling for relevant control variables (i.e., self-concept, risk aversion, materialism, and Honesty-Propriety). As expected, two preregistered online studies (Study 1: N 0.167em=0.167em566; Study 2: N 0.167em=0.167em501) revealed that people with higher Honesty-Humility scores reported more of a negative attitude toward counterfeit luxury. This effect was mainly driven by the Fairness-facet of Honesty-Humility, and only materialism proved to be a further significant predictor for attitude toward counterfeit consumption. The role of the Honesty-Humility factor in research on counterfeit consumption is discussed, directions for future research are given, and as practical implication, first approaches are developed that possible intervention campaigns against counterfeit consumption should consider.
Keywords: 330; Honesty-Humility; Fairness; Counterfeit luxury; Counterfeit consumption